The MIST Guidelines: The Lumbar Spinal Stenosis Consensus Group Guidelines for Minimally Invasive Spine Treatment. Issue 3 (2nd December 2018) - Deer, Timothy R.; Grider, Jay S.; Pope, Jason E.; Falowski, Steven; Lamer, Tim J.; Calodney, Aaron; Provenzano, David A.; Sayed, Dawood; Lee, Eric; Wahezi, Sayed E.; Kim, Chong; Hunter, Corey; et al.
Abstract: Background: Lumbar spinal stenosis (LSS) can lead to compression of neural elements and manifest as low back and leg pain. LSS has traditionally been treated with a variety of conservative (pain medications, physical therapy, epidural spinal injections) and invasive (surgical decompression) options. Recently, several minimally invasive procedures have expanded the treatment options. Methods: The Lumbar Spinal Stenosis Consensus Group convened to evaluate the peer‐reviewed literature as the basis for making minimally invasive spine treatment (MIST) recommendations. Eleven consensus points were clearly defined with evidence strength, recommendation grade, and consensus level using U.S. Preventive Services Task Force criteria. The Consensus Group also created a treatment algorithm. Literature searches yielded 9 studies (2 randomized controlled trials [RCTs]; 7 observational studies, 4 prospective and 3 retrospective) of minimally invasive spine treatments, and 1 RCT for spacers. Results: The LSS treatment choice is dependent on the degree of stenosis; spinal or anatomic level; architecture of the stenosis; severity of the symptoms; failed, past, less invasive treatments; previous fusions or other open surgical approaches; and patient comorbidities. There is Level I evidence for percutaneous image‐guided lumbar decompression as superior to lumbar epidural steroid injection, and 1 RCT supported spacer use in a noninferiority study comparing 2 spacer products currently available. Conclusions: MISTs should be used in a judicious and algorithmic fashion to treat LSS, based on the evidence of efficacy and safety in the peer‐reviewed literature. The MIST Consensus Group recommend that these procedures be used in a multimodal fashion as part of an evidence‐based decision algorithm.